La curva de rendimientos a plazo y las expectativas de tasas de interés en el mercado de renta fija en Colombia 2002-2007 (2008)
How does the yield curve incorporate the expectations on the Colombian future short-term interest rates?. Two theories have been proposed to explain it: the Expectation Hypothesis and the Liquidity Preference Hypothesis. This paper tests both theories for the TES yield curve as well as for the CDT yield curve, using time-series models that account for the persistence and heteroskedasticity of the interest rates. The results support the Liquidity Preference Hypothesis, consistent with the fact that in Colombia long-term rates have been consistently higher than short-term rates. However we found evidence of some predictive power of the long-term rates on the future short term rates, consistent with the Expectation Hypothesis.